Tuning pore structure of aluminosilicate for optimizing thermal energy storage property. (1st November 2022) - Zhen, Liping; Meng, Genping; Yang, Yongjie; Zhang, Mo; Zhou, Bo; Wang, Huazhi
Abstract: Tuning the pore structure of scaffold materials is an effective avenue to preclude the leakage issue of phase change materials (PCMs) and optimize the thermal energy storage capacity of composites for practical applications. Herein, we precisely tuned the pore configuration of nano-aluminosilicate aggerates (n-ASA) by desilication-rearrangement mechanism to systematically investigate the influence of pore size on the energy-storage performance of polyethylene glycol (PEG)-based composites. n-ASA scaffolds with the mean pore size from 11.2 to 27.0, 51.7 and 111.0 nm were synthesized respectively, and the corresponding PCM composites n-ASA*n@PEG were prepared successfully. Among them, n-ASA*1@PEG exhibited the highest heat storage performance on account of the moderate pore size of 27.0 nm and the highest pore volume in all the prepared scaffolds. The load of PEG in the composite reached 81.0 wt%, and the corresponding melting and solidifying enthalpies were 139.8 J/g and 123.8 J/g, respectively. Furthermore, the mechanism of desilication-rearrangement is ideally suited for tailoring the pore size of silica matrixes, and the modulation of pore characteristics would be a feasible protocol to construct efficient energy-storage systems. Highlights: The pore structure of nano-aluminosilicate scaffold n-ASA*n was successfully tuned by desilication-rearrangement mechanism. The scaffolds with the mean pore size of 11.2, 27.0, 51.7 and 111.0 nm have been synthesized, respectively. n-ASA*1@PEG composite with a PEG loading of 81.0 wt% and melting latent heat of 139.8 kJ/kg has been obtained. The pore size of 27.0 nm of the scaffold n-ASA*1is the most appropriate for loading PEG. n-ASA*1@PEG composite exhibits excellent form and thermal stability.